Jackie : public, private, secret - Taraborrelli, J. Randy (St. Martin's Press, 2023)
"From New York Times bestselling author of Jackie, Janet & Lee comes a fresh and often startling look at the life of the legendary former first lady, Jacqueline Kennedy Onassis. Based on hundreds of interviews with friends, family, and lovers over a thirty-year period-as well as previously unreleased material from the JFK Library-Kennedy historian J. Randy Taraborrelli paints an unforgettable new portrait of a woman whose flaws and contradictions only serve to make her even more iconic. "I have three lives," Jackie told a former lover, "public, private and secret." In this revealing biography, readers will become intimately familiar with all three. New insights from the book include: · Jackie's cold feet before her wedding to Jack Kennedy and her secret plan to avoid moving into the White House with him. · Jackie's plan to meet with the woman with whom her husband, Aristotle Onassis, was again having an affair, Maria Callas...and why, in the end, she decided against it. · The truth about the nude photos of Jackie which scandalized her in the 1970s...and which family member had betrayed her by selling them. · Her unusual relationship with Maurice Templesman, which was never what outsiders believed it to be. · The never-before-reported, last-ditch efforts to save Jackie's life with experimental cancer treatments, and the doctor who wouldn't risk jail time in order to treat her. Twenty-nine years after her death and sixty years after the assassination of President Kennedy, Jackie delivers the last word on one of the most famous women in the world"--